Explaining inequity in knowledge, attitude, and services related to HIV/AIDS: a systematic review - Aklilu Endalamaw; Charles F Gilks; Fentie Ambaw; Wondimeneh Shibabaw Shiferaw; Yibeltal Assefa (BMC, 2024)
Abstract Background Equitable service provision and coverage are important responses to end the threat of the HIV/AIDS pandemic. Understanding inequity supports policies and programmes to deliver tailored interventions. There is continuous evidence generation on inequity in HIV/AIDS services. However, there was a lack of evidence on the global picture of inequity in behavioural and biomedical services related to HIV/AIDS. This systematic review assessed inequities in knowledge, attitude, HIV testing, and ART coverage across individual-level social groups and multiple (dis)advantage categories. Methods This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline, with a PROSPERO registration number CRD42024521247. The risk of bias was assessed by using Hoy et al's and Joanna Brigg's quality appraisal checklists for cross-sectional quantitative and qualitative studies, respectively. The search date was from inception to the final database search date (May 29, 2023). The included articles were either quantitative or qualitative studies. We used mixed-methods approach to analyse the data from the review articles. Quantitative descriptive analysis was conducted to estimate frequency of articles published from different countries around the world. Qualitative content analysis of the findings from the original studies was conducted using the PROGRESS plus framework which stands for: place of residence, occupation or employment status, gender, religion, education status, socioeconomic status, and social capital. Results Out of 6,029 articles that were accessed and screened, only 72 articles met the inclusion criteria. More articles on HIV-related equity in knowledge, attitude, testing, and ART were published in developed countries than in developing countries. Individuals from higher-income households had better knowledge about HIV/AIDS. Unfavourable attitudes towards people living with HIV and HIV/AIDS-associated stigma were common among women. HIV/AIDS service coverage (HIV testing or ART coverage) was higher among richer and urban residents. HIV/AIDS-associated stigma and lower levels of knowledge about HIV/AIDS were observed among multiple disadvantageous groups due to the intersection of two or more identities. Conclusions The current review revealed that there have been disparities in HIV/AIDS services between social classes. Ending service disparity towards the global threat of HIV/AIDS demands tailored interventions based on socially disadvantaged groups (e.g., poor, rural dwellers, and women) and intersectional determinants. There is a need to understand the deep-rooted causes of inequity and the challenges that an equity-oriented system faces over time. More studies on inequity are needed, including intersectional inequity, which has been rarely studied in developing countries.